MAC30 Knockdown Inhibits Proliferation and Enhance Apoptosis of Gastric Cancer by Suppressing Wnt/β-Cateninsignaling Pathway. (21st August 2020) - Wu, Xiaohong; Zhang, Yong; Guo, Junping; Yan, Xun; Shen, Li; Zhou, Jianping; Zhao, Jun; Zhuang, Min; Cao, Zhihong
Abstract : Gastric cancer is one of the most frequently diagnosed cancer and poses a serious threat to health system in the world. Upregulation of meningioma-associated protein (MAC30) has been found in many solid tumors and can regulate the proliferation, differentiation, and apoptosis of different tumor cells. Quantitative polymerase chain reaction (qPCR) was used to detect the expression of MAC30 in 68 patients with gastric cancer and their adjacent tissues. Lentiviral vector pGCSIL-shMAC30-GFP of the RNA interference (RNAi) of the MAC30 gene was transfected into gastric cancer BGC-823 cell line and the expression of lentivirus label protein GFP was observed via fluorescence microscope, while cell proliferation and apoptosis were determined with flow cytometry and MTT assay, respectively. Also, related protein expressions on Wnt/ β -catenin signaling pathway were analyzed by Western blot method. The expression of MAC30 was abnormally elevated in gastric cancer tissues, while interfering of its expression could significantly inhibit the proliferation of gastric cancer BGC-823 cell line. However, the promotion of apoptosis by mitochondrial pathway was mediated by Bax/Bcl-2 upregulation. Present work showed the effect of downregulated MAC30 expression on proliferation and apoptosis of gastric cancer cell through Wnt/ β -catenin signaling pathway. Thus, this investigation provides an experimental basis for future development of chemotherapeutic agent on gastric cancer.